Blockade of TRPM7 Alleviates Chondrocyte Apoptosis and Articular Cartilage Damage in the Adjuvant Arthritis Rat Model Through Regulation of the Indian Hedgehog Signaling Pathway - Ma, Ganggang; Yang, Yang; Chen, Yong; Wei, Xin; Ding, Jie; Zhou, Ren-Peng; Hu, Wei (Frontiers in Pharmacology, 2021)
Articular cartilage damage with subsequent impairment of joint function is a common feature of articular diseases, in particular, rheumatoid arthritis and osteoarthritis. While articular cartilage injury mediated by chondrocyte apoptosis is a known major pathological feature of arthritis, the specific mechanisms remain unclear at present. Transient receptor potential melastatin-like 7 channel (TRPM7) is reported to play an important regulatory role in apoptosis. This study focused on the effects of TRPM7 on arthritic chondrocyte injury and its underlying mechanisms of action. Sodium nitroprusside (SNP)-induced rat primary chondrocyte apoptosis and rat adjuvant arthritis (AA) were used as in vitro and in vivo models, respectively. Blockage of TRPM7 with 2-APB or specific siRNA resulted in increased chondrocyte viability and reduced toxicity of SNP. Moreover, treatment with 2-APB enhanced the Bcl-2/Bax ratio and reduced cleaved PARP and IL-6, MMP-13 and ADAMTS-5 expression in SNP-treated chondrocytes. Activation of Indian Hedgehog with purmorphamine reversed the protective effects of 2-APB on SNP-induced chondrocyte apoptosis. Blockage of TRPM7 with 2-APB relieved the clinical signs of AA in the rat model and reduced the arthritis score, paw swelling and spleen index. Similar to findings in SNP-treated chondrocytes, 2-APB treatment increased the Bcl-2/Bax ratio and suppressed cleaved PARP, IL-6, MMP-13, ADAMTS-5, TRPM7, and Indian hedgehog expression in articular cartilage of AA rats. Our collective findings suggest that blockade of TRPM7 could effectively reduce chondrocyte apoptosis and articular cartilage damage in rats with adjuvant arthritis through regulation of the Indian Hedgehog signaling pathway.